Some problems arising in the computer implementation of graphic works - Kusebaev, Уалихан; Zhumabaev, Атағали (Рroblems of engineering and professional education, 2023)
The article reveals the essence of the problem of replacing one curve with another when performing graphic works. To simplify the construction of some more complex curves, they are replaced by less complex, simple ones. With manual graphic work, these replacements are quite suitable. But with the computer execution of drawings by the AutoCAD graphic program, these replacements do not always work correctly. The article also indicates ways to overcome these difficulties.